Comparative evaluation of molecular and antibody based technique for detection of classical swine fever virus infecting pigs of NE Region, India - BARMAN, N N; GUPT, R S; SINGH, N K; TIWARI, A K; SINGH, R K; DAS, S K (The Indian Journal of Animal Sciences, 2011)
In the present study a comparative evaluation was made between antibody-based and nucleic-acid based technique for detection of CSFV. Field tissue and leukocyte samples (120) were collected from CSF suspected outbreaks. The tests showed 64.16% positive in direct FAT, 58.33% in S-ELISA and 75.83% in nested RT-PCR. The viral RNA as well as antigen was mostly detected in the extract of tonsil and mesenteric lymphnodes followed by kidney, spleen, ileum and leucocytes. The study indicated that molecular based technique using E2 specific primer could specifically detect CSFV genome and in higher percentage comparing the polyclonal antibody based techniques like direct FAT and S-ELISA.